Student and Faculty Member Perspectives on Lecture Capture in Pharmacy Education - Marchand, Jon-Paul (American Journal of Pharmaceutical Education, 2014)
Objectives. To examine faculty members’ and students’ use and perceptions of lecture recordings in a previously implemented lecture-capture initiative. Methods. Patterns of using lecture recordings were determined from software analytics, and surveys were conducted to determine awareness and usage, effect on attendance and other behaviors, and learning impact. Results. Most students and faculty members were aware of and appreciated the recordings. Students’ patterns of use changed as the novelty wore off. Students felt that the recordings enhanced their learning, improved their in-class engagement, and had little effect on their attendance. Faculty members saw little difference in students’ grades or in-class engagement but noted increased absenteeism. Conclusion. Students made appropriate use of recordings to support their learning, but faculty members generally did not make active educational use of the recordings. Further investigation is needed to understand the effects of lecture recordings on attendance. Professional development activities for both students and faculty members would help maximize the learning benefits of the recordings.